SIMPLE VIBRATING TABLE FOR CHOCOLATE MOULDING - Imran Thamrin; Muh Ruslan Yunus; Alfrida Lulung Sampe Barra (Balai Besar Industri Hasil Perkebunan, 2018)
This work deals with design of a simple vibrating table prototype for chocolate moulding. Designed for small scale and home made chocolate industry, the main components of the equipment are a 50 x 40 cm vibration table, a 1 HP vibration electric motor, four 7 inch dia. rubber vibration supports, a vibration control system with frequrecies from 0 to 50 Hz, and a frame. The table heigh is 60 cm. Experiments for chocolate moulding using the equipment were conducted to form 2 x 15 pieces of chocolate bars (weighted 22 gram) from dark and milk chocolates, respectively. Vibration frequencies were set from 20 to 50 Hz and durations from 2 to 20 minutes of vibration. Sensory evaluation indicated the high integrity and fine shape levels of the moulded chocolate were given at minimum 40 Hz and 2 minutes and at 35 Hz and minimum 5 minutes of vibration using dark chocolate (107.68 ps in viscociity), and at minimum 40 Hz and 5 minutes and at 45 Hz and minimum 4 minutes of vibration using milk chocolate-1 (115.23 ps in viscocity)Key words : simple vibrating table, chocolate moulding